2000
DOI: 10.1046/j.1365-8711.2000.03536.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface trapping and leakage of low-frequency g modes in rotating early-type stars--I. Qualitative analysis

Abstract: A qualitative study of the surface trapping of low‐frequency non‐radial g modes in rotating early‐type stars is undertaken within the Cowling, adiabatic and traditional approximations. A dispersion relation describing the local character of waves in a rotating star is derived; this dispersion relation is then used to construct propagation diagrams for a 7‐M⊙ stellar model, which show the location and extent of wave trapping zones inside the star. It is demonstrated that, at frequencies below a cut‐off, waves c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Here, we detect a clear series of 36 frequencies (listed in Table 1) which follow a characteristic period spacing pattern (see Figure 4). There is a distinct cutoff in power toward longer periods at the frequency − 0.63051(2) day 1  ( μ 7.2976(2) Hz), which we interpret as a good proxy of the buoyancy cutoff frequency (e.g., Hansen et al 1985;Townsend 2000). This cutoff value is higher than the one of KIC 10526294 by − 0.16 day 1  ( μ 1.85 Hz), which must reflect a difference in mode energy leakage from the stellar atmosphere due to the difference in evolutionary state and/or rotation.…”
Section: A Series Of Gravity Modesmentioning
confidence: 75%
See 1 more Smart Citation
“…Here, we detect a clear series of 36 frequencies (listed in Table 1) which follow a characteristic period spacing pattern (see Figure 4). There is a distinct cutoff in power toward longer periods at the frequency − 0.63051(2) day 1  ( μ 7.2976(2) Hz), which we interpret as a good proxy of the buoyancy cutoff frequency (e.g., Hansen et al 1985;Townsend 2000). This cutoff value is higher than the one of KIC 10526294 by − 0.16 day 1  ( μ 1.85 Hz), which must reflect a difference in mode energy leakage from the stellar atmosphere due to the difference in evolutionary state and/or rotation.…”
Section: A Series Of Gravity Modesmentioning
confidence: 75%
“…This cutoff value is higher than the one of KIC 10526294 by − 0.16 day 1  ( μ 1.85 Hz), which must reflect a difference in mode energy leakage from the stellar atmosphere due to the difference in evolutionary state and/or rotation. Townsend (2000) indeed concluded that the Coriolis force increases the cutoff frequency, although not so much for prograde sectoral modes. This is only the fourth main sequence B-type star where we find such a series of period spacings (after HD 50230, HD 43317, and KIC 10526294 by Degroote et al 2010;Pápics et al 2012Pápics et al , 2014.…”
Section: A Series Of Gravity Modesmentioning
confidence: 93%
“…with c s being sound speed at the surface (Townsend 2000). Among the cases of k = −1, −2, −3 the frequency gap to m f rot (i.e., ν crit ) is smallest for k = −3 because the limiting value of λ is smallest (eq.…”
Section: R-mode Oscillations In White Dwarfsmentioning
confidence: 99%
“…MT Com was discovered as a bright Extreme Ultraviolet (EUV) transient in 1994 with ROSAT (Dahlem et al 1995), which is regarded as a normal dwarf nova outburst (Wheatley et al 2000). From optical time-series photometry in 2000-2004, Patterson et al (2005a detected many short period signals mainly around 1344, 1236, and 668 s (0.744, 0.809, and 1.497 mHz, respectively). These periodicities as well as those obtained by Szkody et al (2010) are shown in the lower panel of Fig.…”
Section: Mt Com (= Re J1255+266)mentioning
confidence: 99%